Covered self-expandable metal stents for pancreatic duct stricture: a systematic review and meta-analysis - Tringali, Alberto; Costa, Deborah; Rota, Matteo; Adler, Douglas G.; Costamagna, Guido (Endoscopy International Open, 2022)
Background and study aims Placement of a covered (C)-self-expandable metal stent (SEMS) has been recently investigated as an alternative endoscopic treatment for main pancreatic duct stricture (MPDS) in chronic pancreatitis. Our aim was to carry out a systematic review and meta-analysis of studies quantifying efficacy and safety of C-SEMSs in the management of MPDS.Methods A multiple database search was performed, including MEDLINE, Embase and Cochrane Library, from January 2000 to September 2020, to identify studies reporting the efficacy and safety of C-SEMSs in patients with MPDS. Stricture and pain resolution were investigated. Other outcomes included technical success, stent migration, stricture recurrence and need for repeated stent placement. Pancreatitis, severe abdominal pain requiring stent removal and de-novo stricture were recorded as complications.Results Nineteen studies were identified, which included a total of 300 patients. C-SEMSs showed a pooled stricture resolution rate of 91 % [95 % confidence interval (CI), 85 %–96 %] and a pooled pain resolution rate of 92 % (95 % CI, 85 %–98 %). The pooled proportion for stricture recurrence was equal to 6 % (95 % CI, 1 %–14 %), while stent migration occurred in 33 of 300 patients, the pooled proportion being 7 % (95 % CI 1 %–15 %). The pooled mean stent duration was 133 days (95 % CI, 100–166 days). The most common complication was pancreatitis (3 %, 95 % CI 0 %–8 %), while de-novo stricture pooled proportion was 2 % (95 % CI, 0 %–5 %).Conclusions C-SEMSs are effective and safe in the treatment of MPDS. However, there is a significant need for further high-quality, well-designed studies to produce evidence-based data on short and long-term efficacy, safety, costs of C-SEMSs, and also optimal stent duration.